2011
DOI: 10.1007/s10072-011-0740-z
|View full text |Cite
|
Sign up to set email alerts
|

The roles of P2X7 receptor in regional-specific microglial responses in the rat brain following status epilepticus

Abstract: Recently, we have reported that astroglial activations in response to status epilepticus (SE) show regional-specific manners in the rat hippocampus. However, it is unknown that microglial responses to SE would show regional-specific patterns. Therefore, the present study was designed to elucidate the regional-specific microglial activation and relationship between P2X7 receptor functions and SE-induced microglial responses in the rat brain. Following SE, microglia appeared amoeboid or phagocytic in the dentate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Activation of the pore-forming function of the P2X 7 R was also found to be required for microglial proliferation (Monif et al, 2009). Consistent with this model, blockade of P2X 7 R reduces microglia activation after status epilepticus (Kim et al, 2009; Choi et al, 2012; Engel et al, 2012a). Targeting the pore-forming functions of the P2X 7 R may therefore be a novel approach to limit microglia responses following status epilepticus.…”
Section: Glia-related Functions Of the P2x7r In Status Epilepticusmentioning
confidence: 63%
See 1 more Smart Citation
“…Activation of the pore-forming function of the P2X 7 R was also found to be required for microglial proliferation (Monif et al, 2009). Consistent with this model, blockade of P2X 7 R reduces microglia activation after status epilepticus (Kim et al, 2009; Choi et al, 2012; Engel et al, 2012a). Targeting the pore-forming functions of the P2X 7 R may therefore be a novel approach to limit microglia responses following status epilepticus.…”
Section: Glia-related Functions Of the P2x7r In Status Epilepticusmentioning
confidence: 63%
“…KA, intra-peritoneal KA; Pilo, Pilocarpine; i.p. Pic, intra-peritoneal Picrotoxin; IgG-P2X 7 , anti-P2X 7 antibodies; Il-1β, interleukin-1beta; qPCR, quantitative polymerase chain reaction; IH, Immunohistochemistry; TNF-α, Tumor necrosis factor alpha; W, Western blot .aCavaliere et al, 2007;bLalo et al, 2008;cEngel et al, 2012a;dAvignone et al, 2008;eKanjhan et al, 1999;fRubio and Soto, 2001;gDona et al, 2009;hSeguela et al, 1996;iCollo et al, 1996;jLe et al, 1998;kUlmann et al, 2013;lGuo et al, 2008;mArmstrong et al, 2002;nYu et al, 2008;oJimenez-Pacheco et al, 2013;pRappold et al, 2006;qKim and Kang, 2011;rChoi et al, 2012;sKim et al, 2011a;t Kim et al, 2011b .…”
Section: Expressional Response Of P2x Receptors Following Status Epilmentioning
confidence: 99%
“…Previous studies have shown that P2X7R antagonists trigger anticonvulsant effect, reducing electrographic and behavioral seizures, microglia activation, decrease IL-1β production and prevent cell damage resulting from seizures [14,15,33,38,41,42]. Studies using P2X7R (Pfizer) [46] knockout mice also show reduction in the severity of seizures compared to wild-type mice [33].…”
Section: Discussionmentioning
confidence: 84%
“…There are many studies aimed at elucidating the role of P2X7R in epilepsy using agonists and antagonists. The activation of P2X7R with Bz-ATP (P2X7R agonist) causes microglial activation, enhances TNF-α immunoreactivity, reduces astrocytes, and intensifies seizures expression [19,[38][39][40]. Conversely, P2X7R blockage promotes anticonvulsant effects and reduces electroencephalographic and behavioral seizures, IL-1β production, microglial activation, recruitment and infiltration of neutrophils into the frontoparietal cortex, and damage resulting from seizure [14,15,33,38,[41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation